EFEKTIVITAS VARIASI UMPAN PADA PYRAMID TRAP TERHADAP JUMLAH LALAT YANG TERTANGKAP DI PASAR PURI BARU PATI TAHUN 2025: EFEKTIVITAS VARIASI UMPAN PADA PYRAMID TRAP TERHADAP JUMLAH LALAT YANG TERTANGKAP DI PASAR PURI BARU PATI TAHUN 2025 - Melinda Ayuningtias; Nur Hilal; Bayu Chondro Purnomo; Fitri Asmaul Janah (Jurnal Sanitasi Profesional Indonesia, 2025)
Fly control is important to prevent the spread of disease, one of which is through mechanical traps such as Pyramid Trap. The effectiveness of this trap is influenced by the type of bait used. This study aims to determine the effectiveness of bait variations in Pyramid Trap on the number of flies caught. This type of research is a Quasy Experiment with Nonequivalent Control Group Design. The data analysis used is Annova Factorial and further testing with Post Hoc LSD. Showed that shrimp bait attracted the most flies, namely 11 flies. Fish offal and chicken offal baits have the same fly catch, which is 4 flies, and Pyramid Trap without being baited or as a control gets a catch of 1 fly. After statistical tests, there were significant differences (p < 0.05) in the control with shrimp, shrimp with fish offal, and shrimp with chicken offal. There was no significant difference (p > 0.05) between control with fish offal, control with chicken offal, and fish offal with chicken offal. Conducting pre-studies and selecting locations with higher fly densities so that the effectiveness of the bait can be tested optimally.